Makna Agama dalam Kehidupan Modern - Diana Ana Sari (Cakrawala: Jurnal Studi Islam, 2019)
Religion is not only a belief but a medium that makes people able to feel God's presence. The view of religion must be lived and practised in everyday life. The practice in modern life, peoples’ perspective is different in interpreting the religion, there are people who view religious beliefs as something that must be practised in ritual worship. Modern life challenges the society who is spoiled with technology, the crisis of meaning causes religion to become a necessity but only a formality. In anticipating all forms of erosion of faith, each person has different ways to determine the purpose of his life, so that different attitudes arise in interpreting religion